2013
DOI: 10.24135/pjr.v19i1.248
|View full text |Cite
|
Sign up to set email alerts
|

Online coverage of the 2008 Olympic Games on the ABC, BBC, CBC and TVNZ

Abstract: Online coverage of the 2008 Olympic Games on the ABC, BBC, CBC and TVNZ The same pervasive strategies that relegate women's sports coverage to secondary status in the traditional sports media are apparent in online coverage. Content analysis of the extent and nature of 2008 Olympic Games coverage by four national public broadcasters shows men and their sports were the story in Beijing. The gender gap in story numbers favoured male athletes by a margin of four to one. Men's achievements were given more prominen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 16 publications
(34 reference statements)
1
23
1
Order By: Relevance
“…Caple et al (2011), Lumby et al (2010), and Paterson and Matzelle (2014) indicated that Australian sports media represented female athletes with minimal gender stereotypical descriptions, contradicting findings uncovered in the current study. In the descriptive analyses of descriptors pertaining to personality or physicality, compared to male athletes, female athletes’ emotion and background were discussed with a high frequency, which is consistent with findings uncovered in both Australia and the United States (MacArthur et al, 2016; Jones, 2013). Emphasizing female athletes’ appropriate femininity such as emotionality and non-sport-related aspects such as background were perceived as two persistent rules in representing female athletes (Bruce, 2016), which could potentially prime the audience with the stereotype that female athletes are not psychologically as stable as male athletes.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Caple et al (2011), Lumby et al (2010), and Paterson and Matzelle (2014) indicated that Australian sports media represented female athletes with minimal gender stereotypical descriptions, contradicting findings uncovered in the current study. In the descriptive analyses of descriptors pertaining to personality or physicality, compared to male athletes, female athletes’ emotion and background were discussed with a high frequency, which is consistent with findings uncovered in both Australia and the United States (MacArthur et al, 2016; Jones, 2013). Emphasizing female athletes’ appropriate femininity such as emotionality and non-sport-related aspects such as background were perceived as two persistent rules in representing female athletes (Bruce, 2016), which could potentially prime the audience with the stereotype that female athletes are not psychologically as stable as male athletes.…”
Section: Discussionsupporting
confidence: 65%
“…In the Australian media coverage of the Olympics, over a long period, male athletes have typically received far more attention than female athletes, regardless of the platforms of television, print, or online media (Eagleman et al, 2014; Jones, 2013; Lumby et al, 2010; Scott and Kunkel, 2016; Stoddart, 1994; Toohey, 1997). In terms of televised coverage, Toohey (1997) examined the broadcast of the 1988 and 1992 Olympics, finding that women’s sports received 32.9% and 29.7% of the total coverage, while men’s sports received 62.9% and 63.9%, respectively (and the remainder dedicated to mixed-gender/paired competitions).…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, female players’ family members appeared more frequently and their motivation and successes were consistently connected to important males in their lives. This carries the possible implication that females are dependent on others and their athletic ability is attributed, at least partly, to their family or other successful relationships, subverting their images as professional athletes (Jones, 2013; Kinnick, 1998). To a certain extent, such representations frame female athletes as passively susceptible and receptive to the influence of males, representing women as available and accessible for men (Shugart, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Although this could mean more equitable coverage of female athletes, findings have been inconclusive so far. Jones (2013) found that women’s accomplishments in the 2008 Beijing Olympics were given less prominence, and they were associated with traditional stereotypes, such as being emotionally weaker. Kian et al (2011) found that female tennis players at the 2007 US Open were given considerably less coverage on three popular sports websites and three newspapers.…”
Section: Online Mediamentioning
confidence: 99%